FROM CHILDHOOD TO TWEENHOOD: AN EXAMINATION OF THE IMPACT OF MARKETING FASHION TO TWEENS ON TWEEN SELF-IMAGE AND MOTHER-CHILD INTERACTIONS - Clancy, Jane Sarah (My University, 2011)
Scholars and laypersons are increasingly concerned about the marketing of inappropriate adult fashions directly to tweens, children between the ages of eight and thirteen. Using a symbolic interactionist approach, I consider strategies used to market tween fashion images, and their influence on tween self-image and mother-child relationships.
Through content analysis of images in two magazines, Today's Parent and Tiger Beat, I establish that contradictions exist between traditional images of childhood as a time of innocence, and more recent adult or sexualized images of tweenhood; that both these types of representations are gendered; and that both reinforce gender roles in childhood and tweenhood alike.
Through qualitative interviews with mothers and tweens, I explore the meanings they associate with tween fashion and their influence on tween self-image. Both mothers and tweens are somewhat influenced by marketing strategies that use brands, logos and celebrity role models to market tween fashion. However, mothers use maternal "gatekeeping" strategies such as solo shopping, and control of financial resources, to mitigate the influence of fashion marketing on their tweens, and to avoid disagreements with their children over potentially inappropriate fashion styles.
Tweens themselves actively filter corporate messages based on their own internalized gendered meanings learned through socialization. The opinions of their mothers, primarily, and their peers, influence their assessments of clothing as appropriate or inappropriate, regardless of marketing strategies. Notably, tween girls use internalized gendered meanings to differentiate between fashions that convey a "good girl" image or a "trampy" image, reproducing patriarchal versions of women as madonnas or whores, even at this age. Despite moral panics, a symbolic interactionist approach inspired by the principles of the new sociology of childhood, privileges tweens' voices and reveals them to be embedded within social networks that temper the influence of tween fashion.
Keywords: tweens; fashion; self-image; gender; mother-child interactions; media; Social Psychology and Interaction; Social Psychology and Interaction